Особливості формування структури середньозернистого твердого сплаву вк3 при температурах існування рідкої фази - Бондаренко, В.П.; Ботвинко, В.П.; Литошенко, Н.В.; Прокопів, М.М.; Юрчук, М.О.; Гнатенко, І.О.; Чучуваткіна, Н.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The paper describes the peculiarities of the formation of the medium-grained low-cobalt
WC–3Co cemented carbide at temperatures of 1300–1400, 1450–1470, 150–1550 and 1750 °C which permit formulating the principles of serial production of two-phase WC–Co cemented carbides having optimal carbon – free structure.